1990
DOI: 10.1037/h0079205
|View full text |Cite
|
Sign up to set email alerts
|

Identification patterns of offspring of Holocaust survivors with their parents.

Abstract: The patterns of identification with their parents of a sample of children of Holocaust survivors showed clear differences from those of a control group. As the clinical literature would indicate, these differences suggest a specific character organization rather than psychopathology. An explanation for the lack of agreement on this issue in the empirical literature is proposed and explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0
16

Year Published

1993
1993
2012
2012

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 20 publications
0
18
0
16
Order By: Relevance
“…Conversely, other studies have pointed out that OHS were in no way affected in terms of personal adjustment [18-20] and that differences between OHS and control groups could suggest a specific character organization rather than psychopathology [21,22]. Specific types of interpersonal relations were found in OHS, and were related to the pattern of parental communication regarding the Holocaust [23,24].…”
Section: Introductionmentioning
confidence: 91%
“…Conversely, other studies have pointed out that OHS were in no way affected in terms of personal adjustment [18-20] and that differences between OHS and control groups could suggest a specific character organization rather than psychopathology [21,22]. Specific types of interpersonal relations were found in OHS, and were related to the pattern of parental communication regarding the Holocaust [23,24].…”
Section: Introductionmentioning
confidence: 91%
“…Secondary traumatization has been reported in several generations of combat soldiers in the immediate and long-term aftermaths of World War I1 (Rosenheck, 1986), the Vietnam War (Kulka et al, 1990), and the Israeli-Arab wars (Solomon,Mikulincer,& Waysman,199 1). Profound transgenerational shifts and strains have been documented in families of survivors of the Nazi holocaust (Felsen & Erlich, 1990). Even in the absence of wartime threats and trauma, separation due to military deployment during peacetime can result in stressful shifts in family system structure and dynamics (Ursano et al, 1989).…”
Section: Toms Of Psychosocial Malfunctioning and Even Begin To Accruementioning
confidence: 99%
“…This is particularly important because so many investigators have not observed differences in psychopathological features characterizing children of survivors (13)(14)(15)(16) or in MMPI-derived measures of global mental health (17), anxiety, depression, or adjustment (18) and have thus attributed findings of pathology to methodological bias or other artifacts. Indeed, a common critique of studies of psychopathology in offspring of trauma survivors is that these investigations have primarily used clinical samples who may not be representative of Holocaust offspring in general (16,19).…”
mentioning
confidence: 99%